(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article examines the impact of misrepresentation and mistake on contractual validity within the common law tradition. Through doctrinal analysis and case study methodology, the research explores how English common law distinguishes between these two vitiating factors, the elements required to establish each doctrine, and the remedies available to aggrieved parties. The article traces the evolution of misrepresentation from the stringent fraud standard in Derry v Peek (1889) to the statutory regime under the Misrepresentation Act 1967, which introduced damages for negligent misrepresentations. Concurrently, the analysis addresses the doctrine of common mistake, particularly the narrow test established in Bell v Lever Bros Ltd and the Court of Appeal’s subsequent rejection of an equitable jurisdiction to render contracts voidable for common mistake in Great Peace Shipping Ltd v Tsavliris Salvage (International) Ltd (2002). The findings reveal a fundamental divergence: misrepresentation renders a contract voidable, focusing on the representor’s conduct, whereas common mistake may render a contract void ab initio, focusing on the subject matter’s essential identity. This distinction reflects broader common law commitments to contractual certainty and the allocation of risk.